2013
DOI: 10.1111/maps.12050
|View full text |Cite
|
Sign up to set email alerts
|

Large spinel grains in a CM chondrite (Acfer 331): Implications for reconstructions of ancient meteorite fluxes

Abstract: Abstract-By dissolving 30-400 kg of marine limestone in HCl and HF acid, our group has previously recovered common relict chromite grains (approximately 63-250 lm) from ordinary chondritic micrometeorites that fell on ancient sea floors, up to 500 Myr old. Here, we evaluate if CM group carbonaceous chondritic material, which makes up an important fraction of the micrometeorite flux today, contains analogous grains that can be searched for in acid residues. We dissolved 8 g of CM2 meteorite Acfer 331 in HF, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…For the estimate we used chromite data for ordinary chondrites (1000 grains >63 μm per gram) from Bjärnborg and Schmitz (2013). Considering that the average thickness of the regolith of Eros is estimated at 20-40 m (Robinson et al, 2002) the ∼30 cm of regolith shed off from the Popigai impactor may only represent a small fraction of the entire regolith layer on such a body.…”
Section: Discussionmentioning
confidence: 99%
“…For the estimate we used chromite data for ordinary chondrites (1000 grains >63 μm per gram) from Bjärnborg and Schmitz (2013). Considering that the average thickness of the regolith of Eros is estimated at 20-40 m (Robinson et al, 2002) the ∼30 cm of regolith shed off from the Popigai impactor may only represent a small fraction of the entire regolith layer on such a body.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of the K‐Pg impactor deduced from chromium isotopes is that of a CM‐type chondrite, a meteorite type known to be rich in Mg‐Al‐spinel grains in the 32–63 µm fraction (Trinquier et al 2006; Bjärnborg and Schmitz 2013). In a 103 kg limestone sample spanning the interval 0.0–0.2 m above the top of the K‐Pg boundary clay, 113 chromite grains 32–63 µm were found; however, no Mg‐Al‐spinel grains were recovered.…”
Section: Discussionmentioning
confidence: 99%
“…At present, no evidence of detrital extraterrestrial MgAl 2 O 4 spinels has been reported in the literature, but, as they are present in meteorites, they are likely to exist. A recent attempt has been made by Bjärnborg and Schmitz () dissolving a fragment of CM2 chondrite Acfer 331, to verify if these kinds of meteorites could be considered as a possible source for detrital Cr‐spinels. There, they found Cr‐spinels similar to those previously found in the Ordovician limestones but also several MgAl spinels that lack in the detrital fraction.…”
Section: Discussionmentioning
confidence: 99%